2017
DOI: 10.1007/s11920-017-0767-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-suicidal Self-Injury in Adolescence

Abstract: Purpose of ReviewNon-suicidal self-injury (NSSI) is a common mental health threat among adolescents. This review aims to present the current literature on epidemiology, etiology, and therapeutic approaches with a focus on the period of adolescence.Recent FindingsNSSI is widespread among adolescents both in community as well as in clinical settings with lifetime prevalence rates between 17 and 60% in recent studies. It is influenced by multiple factors including social contagion, interpersonal stressors, neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
187
2
31

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(286 citation statements)
references
References 78 publications
10
187
2
31
Order By: Relevance
“…Both, childhood adversity [28,37] and NSSI [22] are associated with blunted cortisol response to stress. A recent systematic review suggests similar patterns in major depressive disorder and social anxiety disorder [38] -that are both linked to childhood adversity [39] and frequently comorbid with NSSI [40,41] -which may be sex dependent (i.e., hyporesponsive in females, hyperresponsive in males). In contrast, drawing on a sample of male adolescents and young men, we were recently able to show that male patients with internet gaming disorder also show a blunted cortisol stress response [42].…”
Section: Discussionmentioning
confidence: 99%
“…Both, childhood adversity [28,37] and NSSI [22] are associated with blunted cortisol response to stress. A recent systematic review suggests similar patterns in major depressive disorder and social anxiety disorder [38] -that are both linked to childhood adversity [39] and frequently comorbid with NSSI [40,41] -which may be sex dependent (i.e., hyporesponsive in females, hyperresponsive in males). In contrast, drawing on a sample of male adolescents and young men, we were recently able to show that male patients with internet gaming disorder also show a blunted cortisol stress response [42].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding EDs and NSSI, the literature indicates that both conditions emerge in adolescence (Bjarehed & Lundh, ; Brown & Plener, ), and those with disordered eating and NSSI appear to have a younger age of symptom onset (Wright, Bewick, Barkham, House, & Hill, ) and more binge eating and/or purge behaviours (Peebles, Wilson, & Lock, ) than those who engage only in disordered eating behaviours. Previous studies find that less childhood paternal care (Fujimori et al, ), higher parental criticism (Claes, Soenens, Vansteenkiste, & Vandereycken, ), more substance use disorders (Islam et al, ), and depression (Claes, Vandereycken, & Vertommen, ) are widely reported among ED patients with NSSI.…”
Section: Introductionmentioning
confidence: 99%
“…The most common function of NSSI among Swedish adolescents is automatic negative and positive reinforcement such as stopping bad feelings, reliving feeling numb or empty, punishing oneself and feeling something even if it is pain (Zetterqvist et al, 2013), which is concurrent with other international studies (Brown & Plener, 2017).…”
Section: The Function Of Self-injurymentioning
confidence: 77%
“…According to a study of European adolescents (mean age 14.9 years), the prevalence of direct SIB was 27.6%, with 19.7% reporting to use it occasionally and 7.8% repeatedly (Brunner et al, 2014). A recent review study found the lifetime prevalence of NSSI among adolescents to be 17-18%, and 1.5-6.7% met the DSM 5 criteria, but in clinical samples the prevalence of NSSI was as high as 60% (Brown & Plener, 2017). The use of NSSI is more commonly seen among females, especially in clinical samples (Bresin & Schoenleber, 2015).…”
Section: Self-injurious Behaviourmentioning
confidence: 99%
See 1 more Smart Citation